PERAN MAHASISWA MBKM ASISTENSI MENGAJAR UIN SALATIGA DALAM MENUMBUHKAN SEMANGAT KEISLAMAN MELALUI KHUTBAH JUM’AT - Sumardi, Salsabila; Mubarok, Muhammad Nurul; Huda, Muhamamd Nurul; Famularsih, Sari; Suharmoko, Setyo; Rofiqoh, Eka (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
This study aims to describe the role of students in the teaching assistance program in fostering Islamic spirit through Friday sermon activities at SMP Negeri 4 Salatiga. Using a qualitative descriptive approach, research data were collected through direct observation and documentation of sermon activities. The results show that students play a crucial role as planners of religious activities, sermon deliverers, and spiritual guides for students. Their participation contributes to increased religious awareness, discipline, and motivation of students in practicing Islamic teachings. In addition, the implementation of Friday sermons also strengthens the school's religious culture and helps shape Islamic character in students. For students, this activity serves as a platform for learning da'wah (Islamic preaching) and developing pedagogical skills. Overall, the teaching assistance program through Friday sermons has proven effective in bridging religious theory with practice in the school environment. ABSTRAK Pengabdian ini bertujuan untuk menggambarkan peran mahasiswa dalam program asistensi mengajar dalam menumbuhkan semangat keislaman melalui kegiatan khutbah Jum’at Jum’at di SMP Negeri 4 Salatiga. Dengan menggunakan pendekatan deskriptif kualitatif, data pengabdian dikumpulkan melalui observasi langsung dan dokumentasi kegiatan khutbah Jum’at. Hasil pengabdian memperlihatkan bahwa mahasiswa memiliki peran penting sebagai perancang kegiatan keagamaan, penyampai khutbah Jum’at, sekaligus pembimbing rohani bagi siswa. Partisipasi mereka berkontribusi pada meningkatnya kesadaran beragama, kedisiplinan, serta motivasi peserta didik dalam mengamalkan ajaran islam. Selain itu, pelaksanaan khutbah Jum’at Jum’at juga memperkuat budaya religius sekolah dan membantu membentuk karakter Islami pada diri siswa. Bagi mahasiswa, kegiatan ini menjadi wadah pembelajaran dakwah sekaligus pengembangan kemampuan pedagogis. Secara keseluruhan, program asistensi mengajar melalui khutbah Jum’at Jum’at terbukti efektif dalam menjembatani antara teori keagamaan dengan praktiknya di lingkungan sekolah.